Change of stable snow cover destruction dates in Northern Eurasia, 1936–2008: impact of global warming and the role of large-scale atmospheric circulation - V. V. Popova; I. A. Polyakova (Лëд и снег)
Variation of the stable snow cover destruction dates are examined in order to reveal spatial and temporal peculiarities during the observational period, as well as influence of recent global warming and macro-scale atmospheric circulation variation (in the terms of Northern Hemisphere Teleconnection patterns). The close spatial correlation between time-series of the snow cover destruction dates was revealed for the major part of the investigated territory, especially for the regions occupied by plains and low mountains. The most significant spatial correlation is typical for the Russian plain and Western Siberia (Fig. 1, а–в). ), where the radius of the correlation (the distance where correlation coefficient r decreases in e times comparing with the centre, where r = 1 [2]), reaches 1000–1500 km in latitude and 450–700 km in the meridional direction. Significant differences of the correlation between snow destruction dates in various directions relative to the center are also typical major part of the territory. In condition of the current network of meteorological stations significant spatial correlation between time-series of the snow cover destruction dates provides reliable results of liner spatial interpolation. Even in the North of Western Siberia with a rather sparse network correlation between neighboring station data is enough high and interpolation of station data is acceptable (see Fig. 1, в).Relief of surface essentially reduces the spatial homogeneous of the snow cover and its parameters. At the same time, in the case of a dense network of observational stations (for example, in the Transbaikalia) interpolated dates of the snow cover destruction reproduce satisfactorily basic large-scale features of the spatial distribution of this parameter, including influence of mountains (see Fig. 1, г). Only for the Far East and the most northern regions characterized by extremely rare network interpolation of station data may lead to significant errors.Patterns of the means and the standard deviation of the stable snow cover destruction dates (1936–2008) demonstrate principal large-scale features of spatial distribution of this parameter (Fig. 2 а, б). Response of dates of the snow cover destruction on the recent global warming is evidently reflected in their correlation with the surface air temperature in March averaged for investigated area (Fig. 3, а–г ). The statistically significant inverse correlation is observed in a large part of the Russian plain, the southern half of Western Siberia, Transbaikalia, Primorski Krai. Evidently, that indicates the sustainable impact of warming in the early spring on dates of snow cover destruction, though the values of their shift on an earlier date in average are not high. Location of statistically significant changes in dates of the snow cover destruction for 1971–2008 compared to the 1936–1970's. corresponds to the area of significant correlations with temperature in March. More than 10 day shift value is revealed in the west and southwest of Russian Plane and Transbaikalia. During the separate periods, for example 1998–2007 (compared to 1951–1980), shift of the snow cover destruction dates may reach 15–20 days in the south and southwest of the Russian plain, while, in the north-eastern European Russia, on the Kola peninsula, in the north of Western Siberia and Khabarovsk Krai there may be observed inverse changes for a later date about 5–10 days (see Fig. 3, в ).The most notable changes (more than 20 days) observed in the southwest and west of the Russian plain are associated with anomalies of the North Atlantic Oscillation (NAO) (Fig. 6, а–в). Probably, the positive trend of the NAO (in late winter-early spring) since the early 1970 's. is the major atmospheric circulation factor of the revealed changes of the snow cover destruction dates in the south and southwest of the Russian plain during the last decades. Shifts for the later snow cover destruction, observed over the last decade in the north of West Siberia and north-east of the Russian plain, may be explaned by the positive anomalies of the circulation indices Scandinavian and East Atlantic-Western Russia (Fig. 4, а, б; Fig. 5) in the second half of the 1990 's and early 2000 's.